2008
DOI: 10.1186/1742-2094-5-19
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide 1 receptor stimulation reverses key deficits in distinct rodent models of Parkinson's disease

Abstract: Background It has recently become apparent that neuroinflammation may play a significant role in Parkinson's disease (PD). This is also the case in animal paradigms of the disease. The potential neuroprotective action of the glucagon-like peptide 1 receptor (GLP-1R) agonist exendin-4 (EX-4), which is protective against cytokine mediated apoptosis and may stimulate neurogenesis, was investigated In paradigms of PD. Methods Two rodent 'models' of PD, 6-hydroxydopamine (6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
208
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(215 citation statements)
references
References 27 publications
6
208
0
1
Order By: Relevance
“…Studies in rodent models of Parkinson's and Alzheimer's diseases and mouse models of ischaemic stroke have suggested that GLP-1 receptor agonist might have neuroprotective effects and prevent memory impairment (16)(17)(18). However, studies in humans have not supported the use of GLP-1 RA in cerebral diseases (19), except for one clinical trial of 48 weeks, which suggested that exenatide once weekly had positive effects in Parkinson's disease, which were sustained beyond the period of exposure (20).…”
mentioning
confidence: 99%
“…Studies in rodent models of Parkinson's and Alzheimer's diseases and mouse models of ischaemic stroke have suggested that GLP-1 receptor agonist might have neuroprotective effects and prevent memory impairment (16)(17)(18). However, studies in humans have not supported the use of GLP-1 RA in cerebral diseases (19), except for one clinical trial of 48 weeks, which suggested that exenatide once weekly had positive effects in Parkinson's disease, which were sustained beyond the period of exposure (20).…”
mentioning
confidence: 99%
“…Together, the findings of these studies suggest a loss of function in -/-mice and a physiological role for GLP-1R activation in the normal brain, as in the pancreas, that can be augmented by pharmacologic concentrations of agonists and inhibited by antagonists. Recent studies have demonstrated that Ex-4 can induce neurogenesis of neural stem cells both in culture and in the subventricular zone of rat brain after a 6-OHDA insult (38,39) and promote differentiation toward a neuronal phenotype (38), as has been reported for PC12 cells (13). Ex-4's ability to improve dopaminergic markers and function when administered a week or more after 6-OHDA-or cytokine-induced apoptosis, rather than at the time of insult as in our study, is indicative of neuroregenerative action (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent discoveries have highlighted common cellular pathways that potentially relate neurodegenerative processes with abnormal mitochondrial function and abnormal glucose metabolism [2]. In parallel with these advances, a treatment for insulin resistance (exenatide; a GLP-1 agonist) has been proposed as a disease modifying drug in PD, based on multiple in vitro and in vivo studies [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%